Prognostic impact of chronic obstructive pulmonary disease on short-term and long-term outcomes following coronary artery bypass grafting - Mohammad Sadeq Najafi; Arash Jalali; Zahra Karimi; Mohadese Dashtkoohi; Kimia Moradi; Mojgan Ghavami; Saeed Davoodi; Seyed Hossein Ahmadi Tafti; Rasoul Aliannejad (Scientific Reports)
Abstract Chronic obstructive pulmonary disease (COPD) is a common condition that complicates major surgeries like coronary artery bypass grafting (CABG). This study aims to evaluate the impact of COPD on the outcome of CABG. A registry-based retrospective cohort study included individuals who received CABG between 2009 and 2016. Data were collected on patient demographics, intraoperative factors, and postoperative outcomes. Cox proportional hazard with inverse probability weighting (IPW) and propensity score matching (PSM) were conducted to assess the adjusted effect of COPD on 30-day and long-term mortality and major adverse cardiac and cerebrovascular events (MACCE). Moreover, the impact of COPD in smokers and non-smokers on short/long-term outcomes was assessed. Sensitivity analysis was conducted using multiple imputations. In the present investigation, 17,315 patients including 629 with COPD (mean age 69 ± 9.74), were followed up for a median duration of 8.25 years. Although COPD did not increase 30-day mortality and MACCE risk, the models showed that patients with COPD are at a significantly higher risk of long-term mortality and MACCE after CABG (IPW: HR for mortality: 1.53, 95% CI: 1.31–1.79; HR for MACCE: 1.29, 95% CI: 1.12–1.47). After multiple imputations, the mortality and MACCE hazard ratio in IPW analysis remained statistically significant. COPD significantly increases long-term mortality and MACCE following CABG, independent of smoking status.